2008
DOI: 10.2174/1874912700801010038
|View full text |Cite
|
Sign up to set email alerts
|

Role of Oxidative DNA Damage and Antioxidative Enzymatic Defence Systems in Human Aging~!2008-08-08~!2008-10-29~!2008-12-05~!

Abstract: Oxidative stress is regarded as a main causal factor for natural aging. This study tested the hypothesis that healthy elderly people show higher oxidative DNA damage levels and lower antioxidative enzymatic defense capacities than younger ones. In a cross-sectional study, blood samples of 20 older (62-79 years) and 20 younger adults (24-28 years) were compared with respect to oxidative DNA damage in lymphocytes (alkaline elution), oxidative status (serum peroxides), activities of superoxide dismutase (SOD) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Since ADMA competes with L-arginine for binding to nitric oxide synthase (Böger 2007), it may lead to electrons being diverted to molecular oxygen, with consequent increased production of superoxide rather than NO (Vásquez-Vivar et al 1998). The increased superoxide production may in turn call for an increase in SOD activity to facilitate the conversion of superoxide to hydrogen peroxide (Dittmar et al 2008). High SOD activity along with low GPx activity may lead to the accumulation of hydrogen peroxide and hydrogen peroxide-derived reactive oxygen species such as hydroxyl radicals.…”
Section: Discussionmentioning
confidence: 99%
“…Since ADMA competes with L-arginine for binding to nitric oxide synthase (Böger 2007), it may lead to electrons being diverted to molecular oxygen, with consequent increased production of superoxide rather than NO (Vásquez-Vivar et al 1998). The increased superoxide production may in turn call for an increase in SOD activity to facilitate the conversion of superoxide to hydrogen peroxide (Dittmar et al 2008). High SOD activity along with low GPx activity may lead to the accumulation of hydrogen peroxide and hydrogen peroxide-derived reactive oxygen species such as hydroxyl radicals.…”
Section: Discussionmentioning
confidence: 99%
“…This result can be due to the higher catalase activity and SOD/GPx activity ratio. Previous reports showed that SOD/GPx activity ratio is considered a better enzymatic antioxidant indicator than the absolute enzyme activity (de Haan et al, 1995;Dittmar et al, 2008), which can contribute to protect the nicotine group against lipid peroxidation. Moreover, the N offspring showed an increase of plasma albumin and total bilirubin, reinforcing the protection system against the lipid peroxidation.…”
Section: Tablementioning
confidence: 99%
“…The level of SOD was increased in HepG2 cells only at concentration 0.1 mM while in V79 cells it was not increased at all. Dittmar et al [3], who investigated the role of oxidative DNA damage in human aging, revealed that in blood of older people (that contains a higher amount of oxidative DNA lesions) the SOD/GPx ratio is lowered. This means that the activity of GPx is elevated and the amount of DNA lesions is inversely related to SOD activity.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress occurs in a cell or in a tissue if the concentration of the reactive oxygen species (ROS) and free radicals exceeds their antioxidant capability [1]. As the highly reactive forms of oxygen from both exogenous and endogenous sources may be involved in the pathogenesis of many diseases [2] as well as in the process of aging [3], the acquisition of new knowledge about antioxidant defense mechanisms of cells is very important. Research of molecular bases of antioxidant responses may benefit from the use of established cultures of mammalian cells in vitro.…”
mentioning
confidence: 99%